Hubungan Regulasi Emosi Dengan Parenting Stress Pada Ibu Yang Bekerja Sebagai Perawat di Rumah Sakit X - Vieri, Firstya Thurfah; Syarif, Sandra Adetya (Peneliti.net, 2024)
Parenting stress is an axiety and tension that is often experienced by parents, especially for mothers who work while taking care of the house, it can occur due to many factors. One of the factors that can affect stress in parenting is the mother’s ability to manage negative emotions. This research aims to determine the relationship between emotion regulation and parenting stress in mothers who work as nurses in X hospital using 106 respondents. The methods used in this research is quantitative with the aim of seeing the relationship between the two variables, In data analysis process using with helm of IBM SPSS 25. The results in this research show a correlation coefficient value of 0,135 or it can be interpreted that p > 0,05, it is stated that two variables do not have significant relationship.